High-solubility nanostructure lipid carrier as well as preparation and application thereof
Through solvent evaporation and high-pressure homogenization technology combined with chitosan modification, the problem of low loading of traditional nanostructured lipid carriers is solved, significantly improving the water solubility and loading rate of biologically active substances, improving the stability of the carrier and biological stability of the carrier and the biological Accessibility.
Patent Information
- Application Number
- CN202411435474.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-10
AI Technical Summary
When traditional nanostructured lipid carriers are loaded with bioactive substances with poor liposolubleness, the load capacity is low, and the stability and solubility are insufficient, making it difficult to effectively control the release of active substances.
The nanostructured lipid carrier was prepared by solvent evaporation combined with high pressure homogenization, and the loading, stability and solubility were improved by the surface modification of chitosan and crosslinked chitosan.
It significantly improves the water solubility and loading rate of biologically active substances, improves the stability and bioaccessibility of the carrier, delays the release of active substances, and achieves a 10-15-fold increase in water solubility and an excellent loading rate of 10-15%. in the prior art.
Smart Images

Figure CN119279197A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of carrier systems in food processing technology, and in particular to a high-solubility nanostructured lipid carrier and preparation and application thereof. Background Art
[0002] There are bioactive substances in many animals, plants, marine organisms and microorganisms in nature, such as phytosterols, carotenoids, resveratrol, etc. They have anti-inflammatory, lipid-lowering and blood sugar-lowering, antioxidant and other effects, which can significantly promote human health and prevent diseases. However, most of these bioactive substances have low solubility and high crystallinity, which makes them have many limitations in practical application. Therefore, how to improve the solubility of these bioactive substances is a key technology to expand their application.
[0003] Nanostructured lipid carriers (NLCs) are a new generation of delivery systems developed on the basis of solid lipid nanoparticle systems. Solid lipid nanoparticles are a delivery system composed of solid lipids (lipids that are solid at room temperature), aqueous phase, and emulsifiers. Since the ordered crystalline structure of solid lipids provides less storage space for bioactive substances, bioactive substances are easily discharged from the lipid phase during storage, resulting in low loading. NLCs use mixed lipids as carriers. By adding liquid lipids (lipids that are liquid at room temperature) to solid lipids, the disorder of the crystals is increased, and the carrier has higher crystal defects, so that more bioactive substances can be carried, the loading capacity and encapsulation rate of bioactive substances are increased, the water solubility and stability of bioactive substances are improved, and the release of active substances can be better controlled. However, the loading rate of phytosterols in solid lipid nanoparticles prepared by traditional methods, such as the melt emulsification method using monostearate glyceryl, distearate glyceryl and tristearate, is only about 7.5%, and the loading amount of poorly lipid-soluble bioactive substances is still low (Solid lipid nanoparticles for phytosterols delivery: The acyl chain number of the glyceride matrix affects the arrangement, stability, and release). In addition, Peng Jie used soy protein to prepare water-soluble phytosterol nanoparticles, which increased the solubility of phytosterols to 1.174 mg / mL, but the water solubility was still poor (Preparation of phytosterol nanoparticles and their application in soy milk).
[0004] Therefore, it is necessary to develop a delivery carrier with high loading rate, good stability and improved solubility for poorly soluble bioactive substances. Summary of the invention
[0005]
Technical issues
[0006] Compared with solid lipids with orderly crystalline structures, nanostructured lipid carriers can carry more bioactive substances, increase the loading capacity and encapsulation rate of bioactive substances, improve the water solubility and stability of bioactive substances, and better control the release of active substances. However, the nanostructured lipid carriers prepared by traditional methods still have a low loading capacity when loading certain bioactive substances with poor fat solubility. It is necessary to develop a nanostructured lipid carrier with high bioactive substance loading rate, good stability and high solubility.
[0007]
Technical solution
[0008] To solve the above problems, the present invention adopts solvent evaporation method combined with high-pressure homogenization to prepare nanostructured lipid carriers, and simultaneously uses chitosan and cross-linked chitosan to modify the surface of the nanostructured lipid carriers to improve the loading capacity, stability, bioaccessibility and solubility of bioactive substances.
[0009] The first object of the present invention is to provide a method for preparing a highly soluble nanostructured lipid carrier loaded with a bioactive substance, comprising the steps of:
[0010] (1) adding solid fat, liquid fat, bioactive substance and emulsifier to an organic phase, heating and mixing, to obtain a lipid phase; adding the emulsifier to water, heating and mixing, to obtain an aqueous phase; mixing the lipid phase and the aqueous phase, and subjecting them to high-speed shearing to obtain an oil-in-water colostrum;
[0011] (2) subjecting the oil-in-water colostrum to high-pressure homogenization, evaporating the organic phase, and cooling to obtain a primary nanostructured lipid carrier emulsion;
[0012] (3) adding the chitosan acetic acid solution to the primary nanostructured lipid carrier emulsion and stirring evenly to obtain a chitosan modified nanostructured lipid carrier emulsion;
[0013] (4) adding the sodium tripolyphosphate solution to the chitosan modified nanostructured lipid carrier emulsion and stirring to obtain a cross-linked chitosan modified nanostructured lipid carrier emulsion;
[0014] (5) The cross-linked chitosan modified nanostructured lipid carrier emulsion was prepared into a highly soluble nanostructured lipid carrier by freeze drying.
[0015] In one embodiment of the present invention, in step (1), the organic phase is one or both of acetone and anhydrous ethanol.
[0016] In one embodiment of the present invention, in step (1), the solid fat is one or more of glyceryl monostearate, glyceryl distearate, glyceryl tristearate and stearic acid.
[0017] In one embodiment of the present invention, in step (1), the liquid fat is one or more of medium-chain glycerides, sunflower seed oil, linseed oil, and soybean oil.
[0018] In one embodiment of the present invention, in step (1), the bioactive substance is phytosterol or phytosterol ester.
[0019] In one embodiment of the present invention, in step (1), the emulsifier is a hydrophilic emulsifier, a lipophilic emulsifier or an amphiphilic emulsifier.
[0020] In one embodiment of the present invention, in step (1), the emulsifier of the organic phase is one or more of Span 60 and soybean lecithin.
[0021] In one embodiment of the present invention, in step (1), the emulsifier of the aqueous phase is one or more of Tween 80, Poloxamer 188, and sodium caseinate.
[0022] In one embodiment of the present invention, in step (1), the organic phase is acetone and anhydrous ethanol, and the mass ratio of acetone to ethanol is 2:1 to 6:1.
[0023] In one embodiment of the present invention, in step (1), the organic phase is acetone and anhydrous ethanol, and the mass ratio of acetone to ethanol is preferably 4:1.
[0024] In one embodiment of the present invention, in step (1), the solid lipid concentration of the lipid phase is 5 to 10 wt %.
[0025] In one embodiment of the present invention, in step (1), the liquid lipid concentration of the lipid phase is 5-10 wt %.
[0026] In one embodiment of the present invention, in step (1), the concentration of the bioactive substance in the lipid phase is 1 to 5 wt %.
[0027] In one embodiment of the present invention, in step (1), the emulsifier concentration of the lipid phase is 0.2-0.8 wt %.
[0028] In one embodiment of the present invention, in step (1), the emulsifier concentration of the aqueous phase is 1 to 3 wt %.
[0029] In one embodiment of the present invention, in step (1), the mixing volume ratio of the lipid phase to the aqueous phase is 1:5 to 3:5.
[0030] In one embodiment of the present invention, in step (1), the heating temperature is 50-70°C.
[0031] In one embodiment of the present invention, in step (1), the rotation speed of high-speed shearing is 10000-15000 rpm, and the time of high-speed shearing is 2-6 min.
[0032] In one embodiment of the present invention, in step (2), the pressure of high-pressure homogenization is 400 to 600 bar, and the number of high-pressure homogenization is 2 to 6 times.
[0033] In one embodiment of the present invention, in step (2), the vacuum degree of evaporating the organic phase is -0.04 to 0.10 MPa and the temperature is 40 to 50°C.
[0034] In one embodiment of the present invention, in step (2), the temperature for distilling off the organic phase is preferably 45°C.
[0035] In one embodiment of the present invention, in step (3), the chitosan acetic acid solution is prepared by dissolving chitosan in an acetic acid aqueous solution with a concentration of 0.5 to 2 wt %, and stirring for 8 to 12 hours.
[0036] In one embodiment of the present invention, in step (3), the chitosan concentration of the chitosan acetic acid solution is 0.1-2 wt%.
[0037] In one embodiment of the present invention, in step (3), the volume ratio of the chitosan acetic acid solution to the primary nanostructured lipid carrier emulsion is 1:2 to 2:1.
[0038] In one embodiment of the present invention, in step (4), the concentration of the sodium tripolyphosphate solution is 1 to 10 wt %.
[0039] In one embodiment of the present invention, in step (4), the volume ratio of the sodium tripolyphosphate solution to the chitosan modified nanostructured lipid carrier emulsion is 1:100 to 1:2.
[0040] In one embodiment of the present invention, in step (4), the stirring temperature is 20-40° C., the stirring time is 4-6 hours, and the stirring speed is 400-800 rpm.
[0041] In one embodiment of the present invention, in step (5), the freeze-drying temperature is -75 to -85°C, the freeze-drying vacuum is less than 0.1 Torr, and the freeze-drying time is 36 to 48 hours.
[0042] In one embodiment of the present invention, in step (5), the cross-linked chitosan modified nanostructured lipid carrier emulsion is pre-frozen and then freeze-dried, the pre-freezing temperature is -75 to -85°C, and the pre-freezing time is 8 to 16 hours.
[0043] The second object of the present invention is to provide a highly soluble nanostructured lipid carrier loaded with biologically active substances prepared by the above preparation method.
[0044] The third object of the present invention is the application of the above-mentioned highly soluble nanostructured lipid carrier loaded with bioactive substances in the food field.
[0045] In one embodiment of the present invention, the application in the field of food includes bioactive substance-fortified effervescent tablets, yogurt, and meal replacement powder.
[0046] Beneficial effects:
[0047] The present invention provides a highly soluble nanostructured lipid carrier, which loads bioactive substances with poor fat solubility and water solubility into the core of the nanostructured lipid carrier, thereby solving the problems of poor water solubility and low stability of poorly soluble bioactive substances, and making the water solubility of the bioactive substances reach 8.5-11.55 mg / mL, which is 10-15 times higher than the water solubility of bioactive substances loaded by nanostructured lipid carriers in the prior art.
[0048] The invention prepares a highly soluble nanostructured lipid carrier by a solvent evaporation method in combination with high-pressure homogenization, and achieves a loading rate of 10% to 15% for bioactive substances with poor fat solubility and water solubility, which is better than the 10 to 13% loading rate of the nanostructured lipid carrier for bioactive substances in the prior art.
[0049] The present invention covers a layer of chitosan on the surface of the nanostructured lipid carrier, and densifies the surface chitosan layer by adding a crosslinking agent, sodium tripolyphosphate, to further improve the stability of the nanostructured lipid carrier, delay its release, and improve bioavailability. The nanostructured lipid carrier has excellent stability in different food simulants.
[0050] The bioaccessibility of the nanostructured lipid carrier loaded with bioactive substances prepared by the present invention is also greatly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] Figure 1 The present invention is a preparation process of nanostructured lipid carriers for loading bioactive substances.
[0052] Figure 2 X-ray diffraction patterns of phytosterols and nanostructured lipid carriers.
[0053] Figure 3 Differential scanning calorimetry of phytosterols and nanostructured lipid carriers.
[0054] Figure 4 The figure shows the water solubility determination of phytosterols and nanostructured lipid carriers.
[0055] Figure 5 Figure 2 shows the stability of phytosterols and nanostructured lipid carriers in different food simulants. DETAILED DESCRIPTION
[0056] Test method:
[0057] 1. Test methods for particle size, potential and PDI of nanostructured lipid carriers:
[0058] The particle size (nm), zeta potential (mV) and polydispersity index (PDI) of NUs were measured using a Malvern ZetasizerNanoZS90 (Malvern Instruments Ltd., Worcestershire, UK). All samples were diluted 50 times with pure water before analysis to avoid multiple scattering effects. All data are given as the average of three replicate measurements.
[0059] 2. Determination of loading rate and encapsulation efficiency of nanostructured lipid carriers:
[0060] Take 2mL of the newly prepared cross-linked chitosan modified nanostructured lipid carrier, add 10mL of n-hexane, and immediately vortex and oscillate for 5min using a vortex mixer, then let the solution stand for 1-2min to dissolve the unencapsulated bioactive substances. Collect the upper hexane and blow dry with nitrogen. The residue is redissolved with anhydrous ethanol, and phosphorus sulfur iron colorimetric agent is added to the redissolved residue solution. After reacting for 15min, take 200μl and place it in an ELISA plate. Use an ELISA reader to measure the absorbance value of the bioactive substance at the specific active substance absorption wavelength. According to the standard curve (R 2 >0.99) to calculate the content of bioactive substances. The encapsulation efficiency and loading rate are calculated as follows:
[0061]
[0062] Where: W 总生物活性物质 is the mass of bioactive substance added (mg), W 游离生物活性物质 is the mass (mg) of the free and solution bioactive substances not encapsulated in the nanostructured lipid carriers, W lipid is the mass (mg) of the lipid phase formed by solid lipid and liquid lipid.
[0063] 3. Method for determining the water solubility of nanostructured lipid carriers:
[0064] Take the lyophilized powder of nanostructured lipid carrier and dissolve it in water to make the sample reach supersaturation state, shake it fully for 10 minutes, then shake it on a shaker at 37°C for 24 hours, centrifuge it at 10000rpm for 10 minutes, take the supernatant, add 10mL of n-hexane, and immediately use a vortex mixer to vortex and oscillate for 5 minutes, then let the solution stand for 1-2 minutes to dissolve the unencapsulated bioactive substances. Collect the upper hexane and blow it dry with nitrogen. The residue is redissolved with anhydrous ethanol, and the phosphorus sulfur iron color developer is added to the redissolved residue solution. After reacting for 15 minutes, take 200μl and place it in an ELISA plate. Use an ELISA instrument to measure the absorbance value of the bioactive substance at the specific active substance absorption wavelength. According to the standard curve (R 2 >0.99) to calculate the content of biologically active substances,
[0065]
[0066] 4. X-ray diffraction measurement method:
[0067] The formation of nanostructured lipid carriers loaded with bioactive substances was further characterized by powder X-ray diffractometer. An appropriate amount of freeze-dried nanostructured lipid carrier sample loaded with bioactive substances was placed in a detection tank and a copper X-ray tube (Cu Kα1, ) as the X-ray source. Scanning was performed at 0.5° / min in the diffraction angle region of 5° to 40°. The divergence and scattering slits were 0.5°, and the receiving slit was 0.3 mm.
[0068] 5. Differential scanning calorimetry method:
[0069] The crystallinity and melting behavior of the nanostructured lipid carrier loaded with bioactive substances were studied using a differential scanning calorimeter. Approximately 10 mg of freeze-dried nanostructured lipid carrier sample loaded with bioactive substances was placed in an aluminum pan and heated from 20°C to 200°C at a rate of 10°C / min. The measurement was performed at 20.0 mL / min under a nitrogen flow. An empty aluminum pan was used as a reference.
[0070] 6. Stability testing in food simulants
[0071] 10g of nanostructured lipid carrier was mixed with 10g of hydrophilic mimic (10% ethanol solution), alcoholic mimic (20% ethanol solution) or acidic mimic (3% acetic acid solution), stored at room temperature for 7 days, sampled at specified time (12, 24, 36, 48, 72, 96, 120 and 144h), added to 10mL of n-hexane, and immediately vortexed for 5min using a vortex mixer, and then the solution was allowed to stand for 1-2min to dissolve the unencapsulated bioactive substances. The upper hexane was collected and blown dry with nitrogen. The residue was redissolved with anhydrous ethanol, and phosphorus sulfur iron indicator color developer (or no color developer) was added to the redissolved residue solution. After 15min of reaction, 200μl was taken and placed in an ELISA plate, and the absorbance value of the bioactive substance was measured at the specific active substance absorption wavelength using an ELISA instrument, and the content of the bioactive substance was calculated according to the standard curve (R2>0.99) established by the purified bioactive substance.
[0072]
[0073] 7. In vitro Digestion to Determine Bioaccessibility
[0074] Oral digestion stage: The emulsion prepared in step (4) was diluted with PBS (5 mmol, pH = 7.00) to a lipid content of 2% (w / w), mixed with an equal volume of oral working solution preheated at 37°C, adjusted to pH = 6.80, and shaken at 100 rpm at 37°C for 2 min to obtain oral digestion solution. The oral working solution is SSF containing 30 mg / mL mucin, which needs to be dissolved by stirring at 4°C 12 hours in advance.
[0075] Gastric digestion stage: equal volumes of simulated artificial gastric juice preheated at 37°C and oral digestive juice were mixed, the pH was adjusted to 2.50, and incubated at 37°C and 100 rpm for 2 h to obtain gastric digestive juice.
[0076] Small intestinal digestion stage: Take 60 mL of gastric digestive fluid and adjust the pH to 6.99, then add 3 mL of SIF and 7 mL of bile salt solution (53.6 mg / mL) preheated at 37°C. After the pH is readjusted to 6.99, quickly add 5 mL of pancreatic lipase solution (24 mg / mL, lipase activity is 64-256 U / mL) to start intestinal digestion. React at 37°C for 2 hours to simulate the small intestinal digestion stage. During the reaction, use an automatic titration device to continuously add 0.1 mol / L of NaOH to neutralize free fatty acids (FFA) to keep the pH at 6.995-6.999.
[0077] The micellar phase is obtained by centrifuging the inactivated small intestinal digestive juice at 12000g for 60 minutes at 4°C. A small amount of undigested oil can be seen in the upper layer, the middle phase is clear, and the lower phase has white precipitation. The middle clear liquid is sucked with a syringe to obtain the micellar phase. The phytosterols in the micellar phase are extracted with n-hexane, and the PS content in the micellar phase is measured. The PS bioaccessibility is calculated according to the following formula:
[0078]
[0079] Among them C micellar phase is the concentration of PS in the micelle phase, C small intestine is the concentration of PS in the small intestine product.
[0080] Example 1
[0081] A method for preparing a highly soluble nanostructured lipid carrier loaded with a bioactive substance, comprising the steps of:
[0082] (1) Add 3 g of distearic acid glyceryl, 3 g of medium-chain glycerides, 0.2 g of soybean lecithin, and 1 g of phytosterol to 40 mL of an organic phase, wherein the organic phase is an acetone-ethanol mixture with a volume ratio of acetone to ethanol of 4:1, and heat and mix at 60° C. to obtain a lipid phase; add 2 g of Tween 80 to 100 mL of water, heat and mix at 60° C. to obtain an aqueous phase; mix the lipid phase and the aqueous phase at a volume ratio of 2:5, and high-speed shear at 12,000 rpm for 3 min to obtain an oil-in-water colostrum;
[0083] (2) subjecting the oil-in-water colostrum to 500 bar high-pressure homogenization for three times, evaporating the organic phase at 45° C. and a vacuum degree of −0.04 to 0.10 MPa, and cooling to obtain a primary nanostructured lipid carrier emulsion;
[0084] (3) dissolving 0.5 g of chitosan in 100 mL of 1 wt% acetic acid solution, stirring for 10 h to obtain a chitosan acetic acid solution, adding the solution to 100 mL of the primary nanostructured lipid carrier emulsion, stirring evenly, and obtaining a chitosan-modified nanostructured lipid carrier emulsion;
[0085] (4) Add 20 mL of 50 mg / mL sodium tripolyphosphate solution to the chitosan-modified nanostructured lipid carrier emulsion, and stir at 25° C. and 600 rpm for 6 h to obtain a cross-linked chitosan-modified nanostructured lipid carrier emulsion.
[0086] (5) The cross-linked chitosan modified nanostructured lipid carrier emulsion was placed in a refrigerator and pre-frozen at -80°C for 12 hours, and then placed in a cold trap for freeze drying. The cold trap temperature was set to -80°C, the vacuum degree of the cold trap was less than 0.1 Torr, and the emulsion was frozen for 48 hours to obtain a highly soluble nanostructured lipid carrier.
[0087] The mixing volume ratio of the sodium tripolyphosphate aqueous solution and the chitosan modified nanostructured lipid carrier emulsion in step (4) was replaced with 1:50, 1:20, 1:10 and 1:1 to prepare a series of cross-linked chitosan modified nanostructured lipid carriers, whose particle size, PDI and potential data are shown in Table 1.
[0088] Table 1
[0089]
[0090] From the data in Table 1, it can be seen that the optimal mixing ratio of sodium tripolyphosphate aqueous solution and chitosan modified nanostructured lipid carrier emulsion is 1:5 (v:v) according to the particle size, PDI and potential of the nanocarrier.
[0091] Example 2
[0092] A method for preparing a highly soluble nanostructured lipid carrier loaded with a bioactive substance, comprising the steps of:
[0093] (1) Add 3 g of distearic acid glyceryl, 3 g of medium-chain glycerides, 0.2 g of soybean lecithin, and 2 g of phytosterol esters to 40 mL of an organic phase, wherein the organic phase is an acetone-ethanol mixture with a volume ratio of acetone to ethanol of 4:1, and heat and mix at 60° C. to obtain a lipid phase; add 2 g of Tween 80 to 100 mL of water, heat and mix at 60° C. to obtain an aqueous phase; mix the lipid phase and the aqueous phase at a volume ratio of 2:5, and high-speed shear at 12,000 rpm for 3 min to obtain an oil-in-water colostrum;
[0094] (2) subjecting the oil-in-water colostrum to 500 bar high-pressure homogenization for three times, evaporating the organic phase at 45° C. and a vacuum degree of −0.04 to 0.10 MPa, and cooling to obtain a primary nanostructured lipid carrier emulsion;
[0095] (3) dissolving 0.5 g of chitosan in 100 mL of 1 wt% acetic acid solution, stirring for 10 h to obtain a chitosan acetic acid solution, adding the solution to 100 mL of the primary nanostructured lipid carrier emulsion, stirring evenly, and obtaining a chitosan-modified nanostructured lipid carrier emulsion;
[0096] (4) Add 20 mL of 50 mg / mL sodium tripolyphosphate solution to the chitosan-modified nanostructured lipid carrier emulsion, and stir at 25° C. and 600 rpm for 6 h to obtain a cross-linked chitosan-modified nanostructured lipid carrier emulsion.
[0097] (5) The cross-linked chitosan modified nanostructured lipid carrier emulsion was placed in a refrigerator and pre-frozen at -80°C for 12 hours, and then placed in a cold trap for freeze drying. The cold trap temperature was set to -80°C, the vacuum degree of the cold trap was less than 0.1 Torr, and the emulsion was frozen for 48 hours to obtain a highly soluble nanostructured lipid carrier.
[0098] Comparative Example 1
[0099] The difference from Example 1 is that steps (3) and (4) are omitted.
[0100] Comparative Example 2
[0101] The difference from Example 1 is that there is no step (4).
[0102] The chitosan concentration of the chitosan acetic acid solution in step (3) was replaced with 0.005 mg / mL, 0.05 mg / mL, 0.1 mg / mL, 0.3 mg / mL, 0.7 mg / mL and 1.0 mg / mL to prepare a series of chitosan-modified nanostructured lipid carriers, whose particle size and potential data are shown in Table 2.
[0103] Table 2
[0104] Chitosan concentration (mg / mL) Particle size (nm) PDI Potential (mv) 0.05 153.17±2.35 0.254±0.010 -10.56±0.81 0.5 410.88±26.00 0.247±0.034 -6.46±0.35 1 302.56±21.18 0.326±0.010 7.96±0.78 3 257.29±8.97 0.309±0.032 12.77±0.90 5 292.57±13.42 0.312±0.029 13.87±0.47 7 319.49±8.38 0.331±0.006 11.27±0.45 10 333.30±12.22 0.351±0.017 13.73±0.75
[0105] From the data in Table 2, it can be seen that the optimal condition is a chitosan concentration of 5 mg / mL according to the particle size, PDI and potential of the nanocarrier.
[0106] Comparative Example 3
[0107] The difference from Comparative Example 1 is that glyceryl monostearate is used to replace glyceryl distearate.
[0108] Comparative Example 4
[0109] The difference from Comparative Example 1 is that tristearin is used to replace distearin.
[0110] Comparative Example 5
[0111] The difference from Comparative Example 1 is that stearic acid is used to replace distearic acid glyceryl.
[0112] Comparative Example 6
[0113] The difference from Comparative Example 1 is that in step (1), the amount of distearic acid glyceryl is 4 g and the amount of medium-chain glyceride is 2 g.
[0114] Comparative Example 7
[0115] The difference from Comparative Example 1 is that in step (1), the amount of distearic acid glyceryl is 2 g and the amount of medium-chain glyceride is 4 g.
[0116] Comparative Example 8
[0117] The difference from Comparative Example 1 is that in step (1), no phytosterols are added.
[0118] Comparative Example 9
[0119] The difference from Comparative Example 1 is that the solvent evaporation method is replaced by a melt emulsification method, comprising the steps of:
[0120] (1) 3 g of distearic acid glyceryl and 3 g of medium-chain glyceride were added to a beaker and heated to 75° C. to melt, and then 0.2 g of soybean lecithin and 1 g of phytosterol were added thereto and stirred to form a lipid phase; 2 g of Tween 80 was added to 100 ml of water, heated and mixed at 60° C. to obtain an aqueous phase; the lipid phase and the aqueous phase were mixed at a volume ratio of 2:5, and high-speed shearing was performed at 12000 rpm for 3 min to obtain an oil-in-water colostrum;
[0121] (2) The oil-in-water colostrum is subjected to 500 bar high-pressure homogenization treatment for three times and cooled to obtain a primary nanostructured lipid carrier emulsion.
[0122] Table 3 Test results of nanostructured lipid carriers prepared in Examples and Comparative Examples
[0123]
[0124]
[0125] From the data in Table 3, it can be seen that the particle size of Comparative Example 2 is larger than that of Comparative Example 1. This is because chitosan is adsorbed on the surface of the nanostructured lipid carrier to form a loose structure, which increases the particle size of the carrier.
[0126] Compared with Comparative Example 2, Example 1 uses sodium tripolyphosphate to cross-link the chitosan layer to make its structure dense and compact, and both the particle size and PDI are reduced.
[0127] The bioactive substance loading rate of Example 2 is the highest, because the plant sterol esters have good oil solubility and can be better dissolved in the lipid phase.
[0128] For Comparative Examples 1 and 3 to 5, when glyceryl monostearate, glyceryl tristearate and stearic acid were used as solid lipids, the particle size of the nanocarriers increased significantly and the stability decreased significantly. Therefore, these three lipids are not suitable for preparing nanostructured lipid carriers.
[0129] For Comparative Examples 1 and 6-7, when the solid-liquid ratio of the lipid phase decreases, the particle size of the nanocarrier decreases and the encapsulation efficiency of the carrier for the bioactive substance increases. This is because the solubility of the bioactive substance in the liquid lipid is better than that in the solid lipid. As the liquid lipid ratio increases, the amount of the bioactive substance encapsulated in the nanocarrier increases.
[0130] For Comparative Examples 1 and 8, when no biologically active substance is embedded in the system, the particle size of the nanocarrier decreases.
[0131] For Comparative Examples 1 and 9, the phytosterol nanostructured lipid carriers prepared by the solvent volatilization method have a higher loading rate for bioactive substances.
[0132] Table 4 Bioaccessibility test results
[0133] Bioaccessibility (%) Example 1 36.7 Comparative Example 1 13.3 Comparative Example 2 14.9
[0134] The bioaccessibility of free phytosterols is less than 5%. As shown in Table 4, the bioaccessibility of phytosterols is improved after being encapsulated by nanocarriers, among which the phytosterol bioaccessibility of the cross-linked chitosan modified sterol nanostructure lipid carrier (Example 1) is the highest, reaching 36.7%.
[0135] The XRD and differential scanning calorimetry test results of nanostructured lipid carriers and phytosterols are shown in Figure 2 , 3 shown. Figure 2 In the nanostructured lipid carriers prepared in Example 1 and Comparative Examples 1-2, there is no obvious phytosterol diffraction peak. Figure 3 In the above, free phytosterols showed only one melting peak, ranging from 135.27°C to 142.64°C, corresponding to the melting points of several main phytosterol components. However, this melting peak did not appear in the nanostructured lipid carriers prepared in Example 1 and Comparative Examples 1-2, indicating that the phytosterols here no longer exist in the form of crystals. In summary, phytosterols were successfully encapsulated in the three nanostructured lipid carriers.
[0136] Figure 4 The results of the water solubility test of the nanostructured lipid carriers are shown in Table 1. Compared with the untreated phytosterols, the sterol solubility of the three nanostructured lipid carriers prepared in Example 1 and Comparative Examples 1-2 is improved, among which the sterol solubility of the cross-linked chitosan modified nanostructured lipid carrier prepared in Example 1 is the highest, reaching 11.55 mg / mL. This broadens the application of phytosterols in water-soluble foods.
[0137] Figure 5The stability test results of nanostructured lipid carriers in different food simulants. After the nanoparticles were mixed with hydrophilic simulants and alcoholic simulants and stored at room temperature for 7 days, the PS release rate graph showed that the chitosan-modified nanostructured lipid carrier had higher stability than the unmodified nanostructured lipid carrier, among which the cross-linked chitosan-modified nanostructured lipid carrier had the best stability. After the nanostructured lipid carrier was mixed with the acidic simulants, the PS release rates of Comparative Example 1, Comparative Example 2 and Example 1 were 13.71%, 4.93% and 4.35% respectively. The results showed that the cross-linked chitosan-modified nanoparticles could better control the release of PS.
[0138] The embodiments provided above are not intended to limit the scope of the present invention, and the steps described are not intended to limit the execution order thereof. Those skilled in the art may make obvious improvements to the present invention in combination with existing common knowledge, which also fall within the scope of protection defined by the claims of the present invention.
Claims
1. A method for preparing a highly soluble nanostructured lipid carrier loaded with biologically active substances, characterized in that: Includes steps: (1) adding solid fat, liquid fat, bioactive substance and emulsifier to an organic phase, heating and mixing, to obtain a lipid phase; adding the emulsifier to water, heating and mixing, to obtain an aqueous phase; mixing the lipid phase and the aqueous phase, and subjecting them to high-speed shearing to obtain an oil-in-water colostrum; (2) subjecting the oil-in-water colostrum to high-pressure homogenization, evaporating the organic phase, and cooling to obtain a primary nanostructured lipid carrier emulsion; (3) adding the chitosan acetic acid solution to the primary nanostructured lipid carrier emulsion and stirring evenly to obtain a chitosan modified nanostructured lipid carrier emulsion; (4) adding the sodium tripolyphosphate solution to the chitosan modified nanostructured lipid carrier emulsion and stirring to obtain a cross-linked chitosan modified nanostructured lipid carrier emulsion; (5) The cross-linked chitosan modified nanostructured lipid carrier emulsion was prepared into a highly soluble nanostructured lipid carrier by freeze drying.
2. The preparation method according to claim 1, characterized in that: In step (1), the organic phase is one or two of acetone and anhydrous ethanol; the solid fat is one or more of monostearate glyceryl, distearate glyceryl, tristearate glyceryl, and stearic acid; the liquid fat is one or more of medium-chain glycerides, sunflower seed oil, linseed oil, and soybean oil; the bioactive substance is phytosterol or phytosterol ester; and the emulsifier is a hydrophilic emulsifier, a lipophilic emulsifier, or an amphiphilic emulsifier.
3. The preparation method according to claim 1, characterized in that: In step (1), the solid lipid concentration of the lipid phase is 5-10wt%, the liquid lipid concentration is 5-10wt%, the bioactive substance concentration is 1-5wt%, and the emulsifier concentration is 0.2-0.8wt%; the emulsifier concentration of the aqueous phase is 1-3wt%; and the mixed volume ratio of the lipid phase to the aqueous phase is 1:5-3:
5.
4. The preparation method according to claim 1, characterized in that: In step (1), the heating temperature is 50-70° C.; the high-speed shearing speed is 10000-15000 rpm, and the high-speed shearing time is 2-6 min.
5. The preparation method according to claim 1, characterized in that: In step (2), the pressure of high-pressure homogenization is 400 to 600 bar, and the number of high-pressure homogenization is 2 to 6 times; the vacuum degree of evaporating the organic phase is -0.04 to 0.10 MPa, and the temperature is 40 to 50°C.
6. The preparation method according to claim 1, characterized in that: In step (3), the preparation method of chitosan acetic acid solution is to dissolve chitosan in an acetic acid aqueous solution with a concentration of 0.5 to 2 wt%, and stir for 8 to 12 hours; the chitosan concentration of the chitosan acetic acid solution is 0.1 to 2 wt%, and the volume ratio of the chitosan acetic acid solution to the primary nanostructured lipid carrier emulsion is 1:2 to 2:
1.
7. The preparation method according to claim 1, characterized in that: In step (4), the concentration of the sodium tripolyphosphate solution is 1 to 10 wt %; the volume ratio of the sodium tripolyphosphate solution to the chitosan modified nanostructured lipid carrier emulsion is 1:100 to 1:2; the stirring temperature is 20 to 40° C., the stirring time is 4 to 6 hours, and the stirring speed is 400 to 800 rpm.
8. The preparation method according to claim 1, characterized in that: In step (5), the freeze-drying temperature is -75 to -85°C, the freeze-drying vacuum is less than 0.1 Torr, and the freeze-drying time is 36 to 48 hours.
9. A highly soluble nanostructured lipid carrier loaded with biologically active substances prepared by the preparation method of claim 1.
10. Use of the highly soluble nanostructured lipid carrier loaded with bioactive substances according to claim 9 in the food field.